New N-pyrimidinyl stilbazolium crystals for second-order nonlinear optics - Shin, Bong Rim; Kim, Se In; Kim, Dongwook; Jazbinsek, Mojca; Yoon, Woojin; Yun, Hoseop; Yu, In Cheol; Rotermund, Fabian; Kwon, O. Pil (Optics and Laser Technology, 2022)
We report a new π-conjugated cationic chromophore based on phenolic N-pyrimidinyl stilbazolium and its corresponding non-centrosymmetric crystals. The new cationic chromophore, HPR (4-(4-hydroxy-3-methoxystyryl)-1-(pyrimidin-2-yl)pyridin-1-ium), consists of a strong electron donor, the 4-hydroxy-3-methoxyphenyl group based on two electron-donating groups, and a strong electron acceptor, the N-pyrimidinyl pyridinium group based on two electron-withdrawing groups. The HPR chromophore possesses large molecular optical nonlinearity with first hyperpolarizability of up to 264 × 10−30 esu, which is significantly larger than that of the benchmark stilbazolium chromophores. In solution, the HPR chromophore showed co-existence of phenol- and phenolate-like forms with two absorption bands (∼460 and ∼610 nm, respectively). In the crystalline state, all HPR-based derivatives with three different counter anions, N2S (naphthalene-2-sulfonate), VBS (4-vinylbenzenesulfonate), and NBS (3-nitrobenzenesulfonate), exhibit a macroscopic second-order nonlinear optical response. HPR-N2S crystals exhibit non-centrosymmetric monoclinic Pn space group symmetry and large off-diagonal effective macroscopic optical nonlinearity (94 × 10−30 esu), which is approximately four times higher than that of the benchmark stilbazolium crystals. Therefore, the newly developed HPR-based crystals are highly promising materials for second-order nonlinear optical applications.
Keywords: Cationics; Group-based; Non-centrosymmetric crystals; Optical nonlinearity; Organic crystal; Phenolics; Second order nonlinear optics; Second-order nonlinear optical; Stilbazolia; Sulphonates; Chromophores; Nonlinear optics; Organic crystals; Stilbazolium